InflammamiR-146a and -155 Plasma Levels are Associated with Clinical Efficacy of Risankizumab Treatment in Psoriatic Patients: Pilot Study - Federico Diotallevi; Giulia Matacchione; Giovanni Marco d'Agostino; Helena Gioacchini; Anna Campanati; Jacopo Sabbatinelli; Fabiola Olivieri; Annamaria Offidani (Adis, Springer Healthcare, 2023)
Abstract Introduction The key role of microRNAs (miRNAs) in the pathogenesis of psoriasis has been extensively discussed in the literature. Increasing evidence suggests that the analysis of miRNA levels may constitute an innovative approach for exploring the clinical efficacy of anti-inflammatory therapies in patients with psoriasis. However, so far there have been no published studies evaluating the effects of modulating circulating miRNAs and the efficacy of anti-interleukin-23 (anti-IL-23) therapy. The main objective of the present was to evaluate the diagnostic/prognostic relevance of the levels of five circulating candidate miRNAs (miR-21, miR-146a, miR-155, miR-210, miR-378) in psoriatic patients treated with the anti-IL-23 drug risankizumab. Methods A total of eight psoriatic participants were recruited consecutively from January 2021 to July 2021 at the Dermatology Clinic of Università Politecnica delle Marche (UNIVPM) "Ospedali Riuniti" of Marche. Data on anamnestic, clinical and miRNA evaluations before the initiation of risankizumab therapy and after 1 year (January 2021-July 2022) of risankizumab therapy were available for all patients. Results A significant reduction in the signs and symptoms in patients treated with risankizumab was observed after 1 year of treatment, suggesting that the drug is effective for treating psoriasis in a context of real-life clinical evaluation. Plasma levels of the two prototypical inflammamiRs, miR-146a and miR-155, were significantly reduced after 1 year of risankizumab therapy. Also, in patients before treatment, a significant positive correlation was found between circulating levels of miR-210 and miR-378 and disease severity scores. Conclusions Our results reinforce the notion that specific circulating miRNAs could have clinical relevance as diagnostic/prognostic biomarkers of psoriatic disease and suggest the potential relevance of these miRNAs as biomarkers of treatment response.